CXCL14 facilitates the growth and metastasis of ovarian carcinoma cells via activation of the Wnt/β-catenin signaling pathway - Li-Na Gao; Man Hao; Xiao-Hui Liu; Li Zhang; Yan Dong; Yu-Fang Zhang; Xiao-Chun He (BMC, 2021)
Abstract Background There is an urgent need to identify potential targets in anticancer therapy to improve the survival and prognosis of patients with ovarian cancer (OC). Herein, we investigated the functional significance of chemokine (C-X-C motif) ligand 14 (CXCL14) in OC cell growth and epithelial-mesenchymal transition (EMT). Methods qRT PCR and western blotting was used to detect CXCL14 mRNA level and protein expression, respectively. The functional mechanism of CXCL14 in OC was investigated by CCK-8, colony formation and transwell assays. The migration ability of OC cell was determined using wound healing. The protein expressions of CXCL14 and β-catenin in OC tissues were determined by immumohistochemical staining. Results We demonstrated that high levels of CXCL14 were associated with a worse prognosis in patients with OC. CXCL14 knockdown considerably restrained the growth, migration and invasion of OC cell in vitro. In contrast, ectopic CXCL14 overexpression yielded the opposite results. Investigations to determine the underlying molecular mechanisms revealed that the Wnt/β-catenin signaling pathway is involved in CXCL14-facilitated OC cell invasiveness. Conclusion These data collectively demonstrate that CXCL14 contributes to OC cell growth and metastatic potential by regulating the Wnt/β-catenin signaling pathway.